Comparison between extra mucosal continuous prolene repair versus interrupted through and through silk repair in colonic anastomosis - Nayak, Ashok Kumar; Nayak, Malaya Krishna; Jha, Dharbind Kumar; Kar, Chinmaya; Maharana, Debashree (International Surgery Journal, 2019)
Background: The traditional double layered colonic anastomosis incorporates large amount of ischemic tissue in the suture line causing luminal narrowing and fistula formations. Single layered anastomosis may be done through continuous extramucosal suturing or by interrupted through and through technique using nonabsorbable materials. The single layer of suture has shown to be safe and causes fewer complications. Methods: The study was conducted in the Department of surgery, VIMSAR, Burla during the period from October 2016 to September 2018. All the patients of colonic anastomosis were included in the study. One group consists of extra mucosal continuous prolene repair and other interrupted though and through silk repair. Both groups were followed up and were compared taking different variables. Results: 146 cases of colonic anastomosis were performed, 110 with interrupted through and through silk repair (75.34%) and 36 with continuous extra mucosal prolene repair (24.66%).The mean time taken for silk repair was more (25.67 min) than prolene (15.5 min). The patients of prolene repair had shorter duration (9 days) of hospital stay than silk (12.4 days). The postoperative ileus was more in silk (16.36%) than prolene (5.56%). Anastomotic leak in prolene is less (2.78%) in comparison to silk (8.18%). The bowel movement appeared earlier with prolene (4.2 days) is less than ssilk (5.3 days). Conclusions: The present study shows single layer monofilament thin diameter prolene for different end to end colonic anastomosis has better prognostic panorama in relation to morbidity and mortality, and had an edge over conventional single or bilayere anastomosis.